1985
DOI: 10.1063/1.449661
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure studies of rotational reorientation dynamics: The role of dielectric friction

Abstract: Picosecond, time-resolved, fluorescence depolarization spectroscopy is used to measure the rotational reorientation times of rhodamine 6G (R6G) and p-terphenyl (PTP) as a function of solvent viscosity. The viscosity is varied either by changing the solvent or by changing the pressure in a single solvent. The differences between the two molecules, PTP and R6G, provide a means of evaluating the role of solute structure and solute–solvent interactions on the dynamics of rotational reorientation. The rotational be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 61 publications
6
56
0
Order By: Relevance
“…We tested the set-up and the analysis procedure by measuring the fluorescence lifetime s e of Rh6G at 10 À4 mol=L in ethylene glycol and in ethanol, finding in both cases s e ¼ 3.6 AE 0.1 ns, in agreement with values reported in the literature for the case of negligible energy transfer [14,15]. This ensured that energy transfer effects could be neglected for our experimental geometry [15].…”
supporting
confidence: 70%
“…We tested the set-up and the analysis procedure by measuring the fluorescence lifetime s e of Rh6G at 10 À4 mol=L in ethylene glycol and in ethanol, finding in both cases s e ¼ 3.6 AE 0.1 ns, in agreement with values reported in the literature for the case of negligible energy transfer [14,15]. This ensured that energy transfer effects could be neglected for our experimental geometry [15].…”
supporting
confidence: 70%
“…The dielectric friction can be modeled using continuum theories of NeeZwanzig (NZ) (Nee and Zwanzig, 1970), which treats the solute as a point dipole rotating in a spherical cavity, Alavi-Waldeck (AW) (Alavi and Waldeck, 1991b;1993) model which is an extension of the NZ theory where the solute is treated as a distribution of charges instead of point dipole and the semiempirical approach of van der Zwan and Hynes (vdZH) (van der Zwan and Hynes, 1985) in which fluorescence Stokes shift of the solute in a given solvent is related to dielectric friction. Conversely, the results of neutral and nonpolar solutes deviate significantly from the hydrodynamic predictions at higher viscosities (Waldeck et al, 1982;Canonica et al, 1985;Phillips et al, 1985;Courtney et al, 1986;Ben Amotz and Drake, 1988;Roy and Doraiswamy, 1993;Williams et al, 1994;Jiang and Blanchard, 1994;Anderton and Kauffman, 1994;Brocklehurst and Young, 1995;Benzler and Luther, 1997;Dutt et al, 1999;Ito et al, 2000;Inamdar et al, 2006). These probes rotate much faster than predicted by the SED theory with stick boundary condition and are described by either slip boundary condition or by quasihydrodynamic theories.…”
Section: Introduction To Rotational Dynamicsmentioning
confidence: 86%
“…In the two limiting cases of hydrodynamic stick and slip for a nonspherical molecule, the value of C follows the inequality, 0< C ≤ 1 and the exact value of C is determined by the axial ratio of the probe. It is observed that the experimentally measured rotational reorientation times of number of the nonpolar solutes (Waldeck et al, 1982;Canonica et al, 1985;Phillips et al, 1985;Courtney et al, 1986;Ben Amotz and Drake, 1988;Roy and Doraiswamy, 1993;Williams et al, 1994;Jiang and Blanchard, 1994;Anderton and Kauffman, 1994;Brocklehurst and Young, 1995;Benzler and Luther, 1997;Dutt et al, 1999;Ito et al, 2000;Inamdar et al, 2006) could be described by the SED theory with slip boundary condition (subslip behavior). For a homologous series of solvents such as alcohols or alkanes, the normalized reorientation times decreased as the size of the solvent is increased.…”
Section: Hydrodynamic Theorymentioning
confidence: 99%
See 2 more Smart Citations